Nuclear orphan receptor NR2F6 as a safeguard against experimental murine colitis. Issue 8 (4th August 2017) - Klepsch, Victoria; Gerner, Romana R; Klepsch, Sebastian; Olson, William J; Tilg, Herbert; Moschen, Alexander R; Baier, Gottfried; Hermann-Kleiter, Natascha
Abstract : Objective: Nuclear receptors are known to regulate both immune and barrier functions in the GI tract. The nuclear orphan receptor NR2F6 has been shown to suppress the expression of proinflammatory cytokines in T lymphocytes. NR2F6 gene expression is reduced in patients with IBS or UC, but its functional role and tissue dependency in healthy and inflamed gut have not yet been investigated. Design: Intestinal inflammation was induced in wild-type, Nr2f6 -deficient, Rag1 -deficient or bone marrow-reconstituted mice by administration of chemical (dextran sodium sulfate (DSS)) and immunogenic (T cell transfer) triggers. Disease phenotypes were investigated by survival, body weight, colon length and analysis of immune cell infiltrates. Additionally, histology, intestinal permeability, tight junction proteins, bacterial fluorescence in situ hybridisation, apoptosis, cell proliferation and mucus production were investigated. Results: Nr2f6 -deficient mice were highly susceptible to DSS-induced colitis characterised by enhanced weight loss, increased colonic tissue destruction and immune cell infiltration together with enhanced intestinal permeability and reduced Muc2 expression. T cell transfer colitis and bone marrow reconstitution experiments demonstrated that disease susceptibility was not dependent on the expression of Nr2f6 in the immune compartment but on the protective role of NR2F6 in the intestinal epithelium. Mechanistically, we show that NR2F6 binds to a consensus sequence at −2 kb of the Muc2 promoter and transactivates Muc2 expression. Loss of NR2F6 alters intestinal permeability and results in spontaneous late-onset colitis in Nr2f6 -deficient mice. Conclusion: We have for the first time identified a fundamental and non-redundant role of NR2F6 in protecting gut barrier homeostasis.